2019
DOI: 10.1002/bies.201900041
|View full text |Cite
|
Sign up to set email alerts
|

Hit and Run Transcriptional Repressors Are Difficult to Catch in the Act

Abstract: Transcriptional silencing may not necessarily depend on the continuous residence of a sequence‐specific repressor at a control element and may act via a “hit and run” mechanism. Due to limitations in assays that detect transcription factor (TF) binding, such as chromatin immunoprecipitation followed by high‐throughput sequencing (ChIP‐seq), this phenomenon may be challenging to detect and therefore its prevalence may be underappreciated. To explore this possibility, erythroid gene promoters that are regulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
2
6
0
Order By: Relevance
“…For example, GATA1 facilitates erythropoiesis by activating erythroid genes and repressing those expressed in alternate lineages and HSPCs. [46][47][48][49][50][51][52][53][54] Thus, FBXO11 may repress T-cell and HSPC genes (Figure 3A,C) by facilitating the repressive activities of GATA1. Along the same lines, GATA1 modulates transcription both positively and negatively by displacing GATA2 from many cognate motifs during erythroid maturation, 55,56 and FBXO11 may facilitate this process at some genes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, GATA1 facilitates erythropoiesis by activating erythroid genes and repressing those expressed in alternate lineages and HSPCs. [46][47][48][49][50][51][52][53][54] Thus, FBXO11 may repress T-cell and HSPC genes (Figure 3A,C) by facilitating the repressive activities of GATA1. Along the same lines, GATA1 modulates transcription both positively and negatively by displacing GATA2 from many cognate motifs during erythroid maturation, 55,56 and FBXO11 may facilitate this process at some genes.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint (which this version posted April 4, 2023. ; https://doi.org/10.1101/2023.04.02.535219 doi: bioRxiv preprint had been involved in initiation of repression but eventually were packaged into quiescent chromatin, e.g., via a hit-and-run mechanism (Shah et al 2019), would not be detected.…”
Section: Discussionmentioning
confidence: 99%
“…A fourth limitation is that our inference of repression-related cCREs apply only to those with stable histone modifications. Elements that had been involved in initiation of repression but eventually were packaged into quiescent chromatin, e.g., via a hit-and-run mechanism (Shah et al 2019), would not be detected. A fifth limitation concerns the scale of the studies of epigenetic 29 conservation by correlations of epigenetic states.…”
Section: Discussionmentioning
confidence: 99%
“…The high intranuclear mobility of AR-V7 together with its high transcriptional output, suggest a Hit-and-Run model of transcription, where a transcription factor (TF) transiently binds a DNA sequence to regulate target genes (the ‘hit’), and before vacating the site (the ‘run’) recruits secondary TFs which form stable complex at the regulatory site that sustain a stable long-term effect ( Charoensawan et al, 2015 ). Interestingly, the Hit-and-Run is often applied to transcriptional repressors, where gene silencing does not necessarily require continuous TF residence on chromatin ( Shah et al, 2019 ). Importantly, a recent study showed that AR-V7 functions as a transcriptional repressor in CRPC, preferentially binding several co-repressors compared to AR-fl, likely due to differences in H3K27 acetylation ( Cato et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%